2020
DOI: 10.1039/d0ta07807g
|View full text |Cite
|
Sign up to set email alerts
|

A new high-Li+-conductivity Mg-doped Li1.5Al0.5Ge1.5(PO4)3 solid electrolyte with enhanced electrochemical performance for solid-state lithium metal batteries

Abstract: Li1.5Al0.5Ge1.5(PO4)3 (LAGP), is among the promising solid electrolytes for next lithium battery generation. Nevertheless, its lower bulk and grain boundary ionic conductivity are among the major restrictions for its practical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Among them, oxide and sulfide solid electrolytes are the two most important categories, while oxide solid inorganic electrolytes can be further divided into garnet-type, NASICON-type, and perovskite-type solid electrolytes. Li + conductors of inorganic solid electrolytes like garnet-type, [23][24][25][26][27] perovskite-type, [28][29][30] and NASICON-type 18,[31][32][33][34][35][36] lithium phosphorus oxynitrides, [37][38][39][40][41] and sulfide solid electrolytes (S-SEs) [42][43][44][45][46] are massively studied and the pros and cons of these various types of solid-state electrolytes are briefly summarized in Table 1. In the case of solid electrolytes, the principal features are that they should be high Li + conductivity materials at ambient temperature with insignificant electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, oxide and sulfide solid electrolytes are the two most important categories, while oxide solid inorganic electrolytes can be further divided into garnet-type, NASICON-type, and perovskite-type solid electrolytes. Li + conductors of inorganic solid electrolytes like garnet-type, [23][24][25][26][27] perovskite-type, [28][29][30] and NASICON-type 18,[31][32][33][34][35][36] lithium phosphorus oxynitrides, [37][38][39][40][41] and sulfide solid electrolytes (S-SEs) [42][43][44][45][46] are massively studied and the pros and cons of these various types of solid-state electrolytes are briefly summarized in Table 1. In the case of solid electrolytes, the principal features are that they should be high Li + conductivity materials at ambient temperature with insignificant electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The transport property of Li-ion diffusivity was also analyzed using AIMD simulations. The diffusion coefficient ( D ) and activation energy for Li jumping ( E a ) were calculated from the mean-squared displacement (MSD) obtained from the AIMD simulation using the following equations: 36,37 …”
Section: Resultsmentioning
confidence: 99%
“…Coin cell SS/CPEs/SS (SS, stainless-steel plate electrodes) were assembled to determining the ionic conductivity of the CPEs by alternating current (AC) impedance measurements in the frequency range of 10 MHz to 0.1 Hz with a potential amplitude of 10 mV using a Zahner electrochemical workstation. The ionic conductivity of the composite electrolyte was calculated using eqn (1): 16 where L is the thickness of the electrolyte membrane, R represents the impedance of the symmetrical stainless blocking cells, and S is the electrode area. The coin cell Li/CPEs/SS were assembled to measure the electrochemical window of the CPEs via the linear sweep voltammetry (LSV) technique at a scanning rate of 0.1 mV s −1 using a CHI660E workstation.…”
Section: Methodsmentioning
confidence: 99%
“…Active fillers usually include LATP, LLZO, and LAGP. 14–16 Zhang et al reported that a CPE consisting of LLZO particles and PVDF-HFP polymer matrix exhibited an initial reversible discharge capacity of 120 mA h g −1 at 0.5C and excellent cycling performance for 180 cycles at room temperature. 17 Chen et al studied the Li ion conducting performance of a series of CPEs fabricated by incorporating LLZO into the PEO/LiTFSI matrix.…”
Section: Introductionmentioning
confidence: 99%